Predicados de comunicação em português europeu: nominalizações e nomes autónomos - Reis, Sónia; Mamede, Nuno; Baptista, Jorge (Revista da Associação Portuguesa de Linguística, 2021)
This paper provides an overview of the verbal and noun predicates involving the concept of communication and their distribution in the lexicon‑grammar of European Portuguese. Two key concepts are used: (i) the agent‑speaker semantic role (and other related roles, such as message, and addressee), associated with the subject syntactic slot of these predicates; and (ii) the possibility of the verb to enter a verbum dicendi construction, i.e., introducing direct speech